Achieving combined biological short-cut nitrogen and phosphorus removal in a one sludge system with side-stream sludge treatment. (15th September 2021) - Lu, Xuanyu; Duan, Haoran; Oehmen, Adrian; Carvalho, Gilda; Yuan, Zhiguo; Ye, Liu
Highlights: Stable P removal (> 120 d) was achieved via nitrite pathway in a single sludge system. The two classical PAOs Accumulibacter and Dechloromonas, were eliminated from the system. Side-stream treatment favours the selection of high FNA-tolerance PAOs. Economic analysis reveals up to 27% saving of this new option for BNR in WWTPs. Abstract: Biological nitrogen (N) removal via the short-cut pathway (NH4 + -N→NO2 − -N→N2 ) is economically attractive in wastewater treatment plants (WWTPs). However, biological phosphorus (P) removal processes remain a bottleneck in these systems due to the strong inhibitory effect of nitrite or its protonated form (HNO2, free nitrous acid - FNA) on polyphosphate accumulating organisms (PAOs). In this study, a novel combined nitrogen and phosphorus removal strategy was verified and achieved in a biological short-cut nitrogen removal system via side-stream sludge treatment with FNA, and the mechanisms impacting this process were investigated. The side-stream FNA treatment process applied here led to a significant reduction in the real sludge retention time (SRT) in the mainstream (approximately 2.7 days) based on the biocidal effect of FNA to the majority of the organisms. This work also found that around 40% of the P uptake activity was still maintained at a much higher FNA level of 38 μg N/L with potential PAOs, which highly broadened the current knowledge of PAOs community. An economic analysis revealed advantages of the proposed as compared to conventional biological nitrogen and phosphorus removal (13% savings in total cost), biological short-cut nitrogen removal (via FNA treatment) with chemical phosphorus precipitation (21% savings) and conventional biological nitrogen removal with chemical precipitation (27% savings). Overall, this study presents a novel and viable retrofit strategy in integrating biological short-cut nitrogen removal with EBPR for next generation WWTPs. Graphical abstract: Image, graphical abstract